(untitled) (Journal of Asian Development Studies, 2023)
The current legal system in Pakistan was brought about by British colonization and is extremely difficult for locals to understand. Several problems and difficulties have tainted it for a long time. Despite significant legislative and judicial reforms, the system has failed to provide victims of crimes with prompt and equitable justice, and severe inadequacies continue to damage Pakistani citizens’ lives. Despite significant legislative and judicial reforms, the system has not been able to provide speedy and equitable justice to the victims of crime, and serious shortcomings continue to affect the lives of the people of Pakistan. The criminal justice system in Pakistan has a long history of poor governance, inflexibility, maladministration, corruption, lack of resources, and misuse of power. Accountability issues and a lack of cooperation between the investigation and prosecution wings in Pakistan’s criminal justice system allow accused persons to flee. The government and the legal profession are responsible for CRPC, PPC, and Qanoon-i-Shahadat reforms to improve efficiency and deliver justice. It is the need of the hour to bring about sweeping reforms in criminal laws and an administrative system to ensure justice is available to all segments of society and assure the people that all rank and file are equal in the eyes of the law.